Untersuchungen mit 15N-Tracern in agrikulturchemischen Systemen - Peschke, Heinz (Acta Agraria Debreceniensis, 2002)
Agricultural chemical states and processes are arranged in open and closed systems. Investigations of state are static systems independent of time, testing of process is dynamic systems dependent on time.In order to follow up special facts and occurrences the stable isotope 15N is suited. It is demarcated of native nitrogen of existing systems.In the report as well as results of experiments with 15N tracers in systems soil, fertilizer, plant and animal and too the path as brigde between soil and fertilizer, fertilizer and plant and soil and plant are represented.